Blood-Oxygenation-Level-Dependent-(BOLD-) Based R2′ MRI Study in Monkey Model of Reversible Middle Cerebral Artery Occlusion. (9th January 2011) - Zhang, Jing; Chen, Ying-min; Zhang, Yun-ting
Abstract : Objective . To investigate the value of BOLD-based reversible transverse relaxation rate (R2′) MRI in detecting ischemic penumbra (IP) in a monkey model of reversible middle cerebral artery occlusion (MCAO) and time evolution of relative R2′ (rR2′) in infarcted core, IP, and oligemia. Materials and Methods . 6 monkeys were used to make MCAO by the microcatheter method. MR scans were performed at 0 h (1 h after MCAO), 1 h, 3 h, 6 h, 12 h, 24 h, and 48 h after reperfusion. R2′ was calculated using quantitative T2 and T2 ∗ maps. Ischemic area was subdivided into infracted core, IP and oligemia. rR2′ was calculated respectively. Results . Reversible MCAO model for 4/6 monkeys was made successfully. rR2′ values were significantly different at each time point, being highest in oligemia followed by IP and infarcted core (P < .05 ). With reperfusion time evolution, rR2′ in infarcted core showed a decreased trend: sharply decreased within 6 hours and maintained at 0 during 6–48 hours (P < .05 ). rR2′ values in IP and oligemia showed similar increased trend: sharply increased within 6 hours, maintained a plateau during 6–24 hours, and slightly increased until 48 hours. Conclusion . BOLD-based R2′ MRI can be used to describe changes of cerebral oxygen extract in acute ischemic stroke, and it can provide additional information in detecting IP. The time evolution rR2′ in infarcted core, IP, and oligemia is in accordance with the underlying pathophysiology.